Vortex-induced vibration and structure instability for a circular cylinder with flexible splitter plates. Issue 174 (March 2018) - Liang, Shengping; Wang, Jiasong; Xu, Bohan; Wu, Wenbo; Lin, Ke
Abstract: The research about response of a circular cylinder fitted with rigid splitter plates has been performed previously to control VIV while a structure instability, galloping has been found under some conditions, which has an increasing interest recently. However, the galloping instability attached with flexible splitter plate (FSP 1 ) is studied scarcely. In the present study, a FSP of different length (0.5 ≤ L/D ≤ 2.5) (where L is the length of splitter plates, D is the external diameter of cylinder) was proposed to control the vortex induced vibration (VIV). It was found that the vibration can be well controlled for L/D ≤ 1.1. As a further increase of length of splitter plates, severe galloping occurs. The amplitude response is even higher than that of bare cylinder. Flow visualization showed that shear layers and vortex shedding are controlled by the wave motion of flexible splitter plates. Unlike the classical galloping, it would not persist for all velocities above a certain value. A simple study about the influence of bending stiffness has shown that the response is very sensitive to bending stiffness. FFT spectrums of streamwise velocity obtained from hotwire tests revealed more harmonic components, other than natural frequency, are present when the cylinder is attached with flexible splitter plates. It may be possible that these higher harmonic components are partly responsible for the more violent response. Highlights: Wind tunnel experiment for vibration response of a circular cylinder attached with FSP. Vibration for the cylinder attached with short FSP is well suppressed. Long FSP would induce a severe vibration (galloping) and FSP would be in a wave motion. More harmonics exist in frequency spectrums for the vibrating cylinder with FSP.